Advancing forensic science: Addressing challenges and embracing emerging technologies - YRKM Sai (Forensic Science Today - Peertechz Publications, 2022)
Forensic science is an essential component of the criminal justice system, providing scientific evidence to support investigations and prosecutions. However, the field faces several challenges, including the potential for human error, sample contamination, and ongoing scrutiny and criticism. In recent years, emerging technologies have offered new opportunities to address these challenges and enhance the effectiveness of forensic science. This article provides an overview of the current state of forensic science, the challenges it faces, and the ways in which emerging technologies, such as rapid DNA analysis, artificial intelligence, micro-X-ray fluorescence analysis, and 3D scanning and printing, are being used to address those challenges. These technologies offer new opportunities to improve the accuracy and reliability of forensic evidence and enable forensic practitioners to analyze evidence more quickly and efficiently.